Surgical Strategy Using Endoscopy to Minimize Fetal Surgical Risks in Treating a Pregnant Woman with Herniated Lumbar Disc Disease - Byeong Sam Choi; Il Choi; Sungjoon Lee (Indian Journal of Neurosurgery)
Abstract Pregnancy poses a special clinical challenge in surgical treatments for spinal diseases. Here we present the case of a 30-year-old woman with a ruptured lumbar disc on the right side of L5–S1. The patient was 18 weeks pregnant. Conservative managements for 3 weeks had failed to relieve her pain. We performed interlaminar percutaneous endoscopic lumbar discectomy (PELD) using spinal anesthesia. The left lateral decubitus position was chosen to minimize abdominal compression. Preoperative magnetic resonance imaging (MRI) taken after attaching few fiducial markers at patient's mid-lower back was used to secure the correct surgical level without X-rays. The surgery was successful, and the patient's pain score on a visual analogue scale was reduced from 9/10 to 3/10. Ultrasonography was used to confirm that the baby was healthy postoperatively. PELD causes less pain, and dose not require general anesthesia, which imposes a higher risk of fetal distress than regional anesthesia. Combination of the interlaminar approach of accessing from the midline and a marking MRI permitted PELD without X-ray imaging. The relative ease of performing surgery on either side of the lateral decubitus position makes PELD more feasible for pregnant patients.